Second Five Year Plan Annual Plan 1956-57 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1956)
The primary object of the First Five Year Plan was to Jay the foundations for building a more progressive and diversified economy. The plan was formulated against the background of a mounting inflation and an acute shortage of food and raw materials. Though the achievements of the first plan have' been significant it is only a beginning for generating a dynamism in the economy which will lift it continually to higher levels of material well-being.
Planning and Development Department, Government of Andhra Pradesh